Comparison study between slender columns and short columns of reinforced concrete circular cross-section supported using carbon fiber polymer fully scale - Al karaki, Alaa (جامعة بوليتكنك فلسطين - ماجستير مباني, 2023)
Many researchers studied and used different materials to strengthen and rehabilitate the concrete column , we know that the concrete column is a structure element that can be deformed from applying loads to it. And there are two types of columns the short and slander. Examples of such materials include carbon polymer fiber concrete (CFRP), glass polymer fiber concrete (GFPR), shape memory alloy (SMA) and ultra high performance concrete (UHPC)... etc . In this thesis, analysis, comparing and investigation to strengthen concrete crucial columns topical scale sample using CFRP from practical experience, comparing results with finite element method. The study of parameters in this research is the type of column short or sender is the main parameter to compering , the strength of concrete using at beginning 24 Mpa and increased to 28 Mpa ,at last we covered the circular column with Carbon Fiber Reinforced Palomar(CFRP) so we can choose the orientation of layer CFRP horizontal, vertical and combined between vertical and horizontal orientation. The results of tested circular column showed the beneficial effects of strengthening the RC column using CFRP, as evident from enhancement of the axial capacity and shifting of the failure mode from brittle to ductile with more stiff behavior.
CD, no of pages 70, 31628, ماجستير مباني 13/2023
Keywords: the slender columns; theshort columns; concrete circular cross-section; carbon fiber